THE ROLE OF RUSSIAN COMPOSITORS' ORCHESTRA WORKS IN THE FORMATION OF PERFORMANCE SKILLS IN SCHOOLS OF MUSIC - Okhunjon Kimsanov; Shodiyor Mahmudjonov (Bright Mind Publishing, 2025)
Orchestral works by Russian composers play a significant role in developing performance skills among students of music schools. These compositions, characterized by their rich textures, thematic depth, and technical complexity, provide young musicians with opportunities to enhance their ensemble playing, dynamic control, and interpretative abilities. The works of composers such as P. I. Tchaikovsky, N. A. Rimsky-Korsakov, S. V. Rachmaninoff, and D. D. Shostakovich serve as essential pedagogical tools in fostering technical precision, musical expression, and artistic sensitivity. The process of rehearsing and performing orchestral pieces allows students to develop discipline, coordination, and an awareness of musical structure and orchestration. In Uzbekistan, Russian orchestral compositions remain integral to the academic curriculum, contributing to the cultivation of well-rounded musicians. This article examines the pedagogical significance of these works, their impact on students' performance skills, and strategies for effectively incorporating them into music education.
Keywords: Orchestral works, Russian composers, performance skills, ensemble playing, musical interpretation, technical development, orchestration, dynamic control, music education, pedagogical approaches.